PENGARUH PENERAPAN SISTEM MANAJEMEN KEAMANAN PANGAN ISO 22000:2005 TERHADAP KUALITAS PRODUK PANGAN PADA DEPARTEMEN PRODUKSI NOODLE PT. JAKARANA TAMA FOOD INDUSTRY (FACTORY) BOGOR - Selviana Ernayanti Aprilia; Samsuri Samsuri; Titiek Tjahja Andari (Jurnal Visionida, 2017)
The purpose of the research is to determine the effect of application food safety management system ISO 22000:2005 to food quality in noodle production departement PT. Jakarana Tama Food Industry (Factory) Bogor. Questioner distributed 100 respondents. Analysis method used is descriptive analysis and verification. The questioner validity and reliability testing and test the classic assumption. Likert scale is used prior to testing with multiple regressions. In order to know the effect of four free variable that is used for dependent variable. Based on the result all indicators expressed validity and reliability, simultaneously with interactive communication (X1), system management (X2), prerequisite programmes (X3) and HACCP principles (X4) have an influence to food quality in noodle production departement PT. Jakarana Tama Food Industry (Factory) Bogor (Y). Partially, only a few prerequisite programmes that gives positive and significant to food quality in noodle production departement.Keywords: Brand Image, Quality Product, Purchasing Decisions